KONSEP KEPEMILIKAN ASSET TETAP DALAM AKUNTANSI SYARIAH - Ramdany Ramdany (STIE Muhammadiyah Jakarta, 2020)
Allah SWT is the absolute owner of property as explained in the Qur'an An-Nisa, 132 explains: